Control program of congenital toxoplasmosis - Navarro, Italmar Teodorico; Breganó, Regina Mitsuka; Mori, Fabiana Maria Ruiz Lopes; Rodrigues, Tercilia Oliveira [UNESP]; dos Santos, Thaís Rabelo [UNESP]; dos Santos, Rodrigo Rabelo [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2013)
Toxoplasmosis is a zoonotic disease caused by coccidia Toxoplasma gondii, that affects almost all homeothermic animal species, including birds, mammals and also humans. The implementation of control programs including preventive measures such as laboratory tests frequently promotes early diagnosis and appropriate indication of adequate antiparasitic treatment to pregnant women, and is, therefore, able to diminish the seriousness of the sequelae of toxoplasmosis in the fetus. Important aspects of the control of congenital toxoplasmosis programs for maternal and neonatal screening, the toxoplasmosis control program were reviewed. © 2013 by Nova Science Publishers, Inc. All rights reserved.